The Economic and Sharia Value of Moslemâs Awareness for Halal Food in Indonesia - Susilowati, Indah; Edy Riyanto, Edy; Kirana, Mayanggita; Mafruhah, Izza; Radam, Alias (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2018)
The concept of halal products or foods is now gaining a worldwide discussion due to its recognition as an alternative benchmark for safety, hygiene and quality assurance of what we consume or drink daily. For a moslem consumer, halal foods and drinks means that the products has met the requirements laid down by the Shariah law. It represents the symbol of hygiene, quality and safety product when produced strictly under the Holistic Halal Assurance Management System. It is expected with halal certification to ensure the halal of food consumed by moslem in Indonesia could increase the sharia and economic values for the moslem in Indonesia. Indonesia is a huge market for halal product, and has just legalized regulation on halal product guarantee. The recent dynamics urge the importance of knowledge of consumerâs behavior on halal product.Â This study is aimed to explore an economic and sharia values of moslem awareness in Indonesia with a pilot project in Semarang City. The standard of halal used are defined from the points of: (1) input or material come from; (2) how to get the input; (3) how to process the input; (4) how to store the input; (5) how to transportage the input; and (6) how to package and serve the input. Mixed-method of quantitative and qualitative had been invoked to analyse the data.The results indicated that the level of awarness for consuming the halal food are vary among the moslem community by her/ his income- and sharia-stratum as perceived by them. It is hardly difficult to aware people of A-B-G-C accordingly for halal food in such high intense of diversity in community in short-term. Of course, a lot of efforts and strong committment among the stakeholders is indeed needed to ensure the halal food consumed by moslem in Indonesia.